To stratify complications of percutaneousnephrolithotomy (PCNL) in a single hospital by use of the modified Clavien grading system - Y Limbu (Society of Surgeons of Nepal, 2016)
Introduction: PCNL is relatively safe but evaluating its complication can be of importance so that we can betteranticipate and act on it.